Air Pollution and Adolescent Development: Evidence from a 3-Year Longitudinal Study in China - Na Ni; Xinli Chi; Wei Liu; Xiumin Cui (MDPI AG, 2021)
This study aimed to investigate the impact of air pollution on the development of adolescents and the mediating role of students' emotional disorders. Participants came from a longitudinal sample group of adolescents (n = 1301) in Southern China from the years 2016 to 2018. They were assessed for the Positive Youth Development and emotional disorders, and air pollution was measured by the Air Quality Index. The results show that students' higher degree of exposure to air pollution was negatively associated with their positive development. Three out of four emotional disorders (i.e., anxiety, neuroticism, and withdrawal) mediate this association. The results suggest that the physical environment can have a paramount influence on the emotional status and overall development of adolescents, calling for intervention programs by policymakers.